The Tenth Hour in John 1:39: From Narrative Detail to Eschatological Symbol - Adam Kubiś (The Biblical Annals, 2025)
This article offers a comprehensive analysis of the reference to ‘the tenth hour’ in John 1:39, a detail frequently dismissed as minor or incidental. The study identifies three principal interpretative approaches: (1) literary or narrative readings, which view the hour as a marker of eyewitness memory, narrative precision, or structural closure; (2) temporal-pragmatic interpretations, which link the hour to historical chronology, social customs (e.g., hospitality, Sabbath observance), or practical details of the disciples’ encounter with Jesus; and (3) symbolic-theological interpretations, which understand the tenth hour as a signal of eschatological or theological significance. The central argument affirms a dual-layered Johannine narrative strategy: the tenth hour functions both as a literal temporal detail and as a symbolic expression of divine revelation, discipleship, and eschatological fulfilment. Drawing from early Jewish texts – including Testament of Adam, 2 Enoch, and the works of Philo – the article offers a new proposal that situates the tenth hour within broader traditions of visionary ascent, divine encounter, and symbolic numerology. The study concludes that the ‘tenth hour’ is not merely a temporal detail, but a deeply theological marker that inaugurates a new era of divine revelation and discipleship.